Gevaarlijke Stilte - Hoff, Rob (Netherlands)
The film follows the peace missions of Max can der Stoel, the first High Commissioner on National Minorities of OSCE, in former Yugoslavia. He tries to find solutions for people who are trapped in a place which is not theirs: Serbs live in houses that once belonged to Croats while Croats live in houses that once belonged to Serbs. Through the eyes of Serbs and Croats, the film illustrates displacement, unhappiness and lack of hope for equitable solutions.
Soros Documentary Fund
Soros Documentary Fund
Keywords: Documentary films